The Influence of Tax Understanding, Service Facilities, and Tax Morale on MSME Taxpayer Compliance - Defany Diah Pramudita; Moh. Danang Bahtiar (Journal of Educational Management Research, 2026)
This study aims to examine the effects of tax understanding, service facilities, and tax morale on the compliance of Micro, Small, and Medium Enterprises (MSMEs) taxpayers. Understanding the factors influencing compliance is crucial for improving tax revenue and promoting responsible business practices. A quantitative research approach was employed, with data collected from micro-scale MSME taxpayers through purposive sampling. The data were analyzed using multiple linear regression to determine both the individual and simultaneous effects of the independent variables on taxpayer compliance. The results indicate that tax understanding, service facilities, and tax morale each have a positive and significant impact on MSME taxpayer compliance. Collectively, these factors contribute substantially to compliance behavior, highlighting the importance of integrating knowledge, accessible services, and ethical awareness in tax management. The findings imply that enhancing taxpayer education, improving the quality of service facilities, and fostering moral awareness among taxpayers can effectively increase compliance levels. These insights provide valuable guidance for policymakers and tax authorities aiming to optimize voluntary tax compliance in the MSME sector.